ADDITIONAL CHARACTERISTICS OF HYBRID COMPOSITES FOR FILLING TEETH UNDER LOCAL MOUNTING CLOCKS - V.F. Makeev; V.S. Kukhta; O.S. Kyrmanov; V.R. Skalsky (Український стоматологічний альманах, 2021)
For the rational use of materials, it is necessary to have data on their ability to resist deformation and destruction. In particular, in each case it is necessary to have information on the stiffness, strength and resistance to destruction of materials in the specified operating conditions of the elements. To determine such strength characteristics of the material, certain studies are carried out.